The relationship between social participation and depressive symptoms among Chinese middle-aged and older adults: A cross-lagged panel analysis - Ding, Yifei; Chen, Lanshuang; Zhang, Zhen (Frontiers in Public Health, 2022)
Objectives: This study examined the mutual effects of social participation and depressive symptoms in middle-aged and older Chinese adults from offline and online perspectives. Reciprocal relationships between depressive symptoms and the four subtypes of offline participation were also examined. Method: Based on China Health and Retirement Longitudinal Study data (CHARLS), this study conducted ID matching for three waves of data from 2013, 2015, and 2018. One thousand nine hundred ninety-nine samples for individuals over 50 were obtained. A series of cross-lagged analyses were conducted to examine the mutual influence of social participation and depressive symptoms. Depressive symptoms were assessed using the short version of the Center for Epidemiologic Studies Depression Scale (CESD-10). The social participation questionnaire included nine items referring to offline participation (8 items) and online participation (1 item). Several demographic variables were adjusted when conducting the cross-lagged analyses. Results: Social and offline participation had significant two-way associations with depressive symptoms. Depressive symptoms had greater impacts on social and offline participation than in the opposite direction. Online participation has a significant one-way impact on depressive symptoms. The relationship between specific types of offline participation and depressive symptoms varied in existence and direction. Discussion: Overall, there was significant bidirectional causality between social participation and depressive symptoms. Social participation, both offline and online, played a positive role in alleviating depressive symptoms. Depressive symptoms also affected the level of social participation to some extent among middle-aged and older Chinese adults over time.